Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Closing Ceremony of International Innovation Festival on Green Technology 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Alhamdulillah, it gives me great pleasure this afternoon to be amongst you and to say a few words in this auspicious occasion that marks the conclusion of the inaugural International Innovation Festival on Green Technology 2016 or I-FINOG, organized by Universiti Malaysia Pahang.